Ablation of neuronal ADAM17 impairs oligodendrocyte differentiation and myelination. Issue 6 (18th December 2019) - Fredrickx, Evelien; Colombo, Elisa; Canevazzi, Paolo; La Marca, Rosa; Pellegatta, Marta; Dina, Giorgia; Podini, Paola; Nave, Klaus A.; Quattrini, Angelo; Taveggia, Carla
Abstract: Myelin, one of the most important adaptations of vertebrates, is essential to ensure efficient propagation of the electric impulse in the nervous system and to maintain neuronal integrity. In the central nervous system (CNS), the development of oligodendrocytes and the process of myelination are regulated by the coordinated action of several positive and negative cell‐extrinsic factors. We and others previously showed that secretases regulate the activity of proteins essential for myelination. We now report that the neuronal α‐secretase ADAM17 controls oligodendrocyte differentiation and myelin formation in the CNS. Ablation of Adam17 in neurons impairs in vivo and in vitro oligodendrocyte differentiation, delays myelin formation throughout development and results in hypomyelination. Furthermore, we show that this developmental defect is, in part, the result of altered Notch/Jagged 1 signaling. Surprisingly, in vivo conditional loss of Adam17 in immature oligodendrocytes has no effect on myelin formation. Collectively, our data indicate that the neuronal α‐secretase ADAM17 is required for proper CNS myelination. Further, our studies confirm that secretases are important post‐translational regulators of myelination although the mechanisms controlling CNS and peripheral nervous system (PNS) myelination are distinct. Abstract : Neuronal ADAM17 promotes oligodendrocyte differentiation and myelination. Neuronal ADAM17 partly acts on Notch/Jagged1 signaling. ADAM17 in immature oligodendrocytes does not participate in CNS myelination.